Antipodean agricultural and resource economics at 60: booming sector economics1. (4th July 2016) - Freebairn, John
Abstract : Contributions of Australian economists to understand the effects of a boom export industry are reviewed. Effects are considered on: the real exchange rate; output, prices and factor incomes of the boom industry, other trade‐exposed industries and nontraded industries; and national income and its distribution. Theoretical models and empirical models are reviewed. Different effects are considered for supply‐side‐ versus demand‐side‐driven booms, and then for the price increase, investment increase and production increase phases of the boom. Evaluations of industry and macroeconomic policy options are canvassed.